Development of Situ Gede Lake Tourism and Local MSMEs through Web-Based Digital Promotion and Data Analysis - Meavi Cintani; Zamrah Mutmainah; I Gusti Ngurah Sentana Putra; Sabrina Adnin Kamila; Lisa Amelia; Sachnaz Desta Oktarina; Anang Kurnia; Agus Mohamad Soleh; Akbar Rizki (Asosiasi Dosen Pengembang Masyarajat (ADPEMAS) Forum Komunikasi Dosen Peneliti, 2026)
Background: The development of tourism at Situ Gede Lake and local MSMEs through a web-based digital promotion and data analysis approach addresses the need for local tourism to compete more effectively. This community service focuses on empowering local MSMEs within the tourism ecosystem using digital technology. Purpose of the Study: This study aims to develop a web-based platform that integrates digital promotion and data analysis to support tourism digitalization at Situ Gede Lake, enhance MSME empowerment, and introduce data-driven visitor trend analysis using the Long Short-Term Memory (LSTM) deep learning method. Methods: The platform was developed using daily visitor data from the Situ Gede Village Office. The LSTM model was applied to forecast tourist numbers through 2026. Socialization and training were conducted on July 3, 2025, with 31 participants from POKDARWIS, MSME actors, village officials, and the community. The web application (https://situgede-ssmi.ipb.ac.id/) integrates a visitor statistics dashboard, MSME catalog, interactive map, event schedule, and waste management education. Results: The dashboard reveals an average of 53 visitors per day, 17 active communities, and estimated daily revenue of 2.5 million rupiah. LSTM predictions indicate a seasonal surge in mid-2026 potentially exceeding 400 visitors per day. MSME actors showed readiness to utilize the digital catalog, and participants responded positively to improved information access. Early findings demonstrate that combining web-based digital promotion and data analysis enhances MSME visibility, supports sustainable tourism development, and strengthens environmental awareness at Situ Gede Lake.